Leadership Today - Marques, Joan; Dhiman, Satinder (Springer, 2017)
The story that today’s workforce is looking for different skills and qualities in its leaders has become abundantly clear in the past decade, not only through a major shift in corporate leadership, but also through shifts in leadership qualities being taught in business schools and topics that leadership scholars focus on these days. According to Daniel Goleman, soft skills are inner- and interhuman skills such as self-awareness, self-regulation, motivation, empathy, and social skills. In 2009, three scholars i conducted a multi-method study with surveys and interviews, in which 11 major European multinational corporations participated. This study underlined the impression that workforce members are really looking for soft skills in their leaders today. The survey part of the study yielded the following compiled list of desired leaders’ qualities: “(1) Acting with integrity. (2) Caring for people. (3) Demonstrating ethical behavior. (4) Communicating with others. (5) Taking a long-term perspective. (6) Being open-minded. (7) Managing responsibly outside the organization.” (p. 11). The interview part of the above-mentioned study yielded fi ve refl exive abilities desired for leaders: “(1) systemic thinking; (2) embracing diversity and managing risk; (3) balancing global and local perspectives; (4) meaningful dialogue and developing a new language; and (5) emotional awareness” (p. 15).
Practices for Personal and Professional Performance